Quaternary Geology and Environmental Health - Kramer, James (Geoscience Canada, 1982)
Summary This discussion considers two aspects ofenvironmental health and Quaternarygeology. One aspect considers the inhala-tion of dusts derived from unconsoli-dated sediments, and the other aspectconsiders ingestion and the "waterfactor". Both of these aspects of environ-mental health require mineralogical andgeochemical information regardingQuaternary sediments, and most oftenthere are little data available.